Fabrication and characterization of carbon-based counter electrodes prepared by electrophoretic deposition for dye-sensitized solar cells - Kim, Hyunkook (Springer, 2012)
Three different carbon-based counter electrodes are investigated in light of catalytic activities such as electrochemical frequencies and interface impedances. We fabricated carbon-based counter electrodes of dye-sensitized solar cells [DSSCs] using graphene, single-walled carbon nanotubes [SWNTs], and graphene-SWNT composites by electrophoretic deposition method. We observed the optical and electrochemical properties of the carbon-based counter electrodes. The DSSC with the graphene-deposited counter electrode demonstrated the best conversion efficiency of 5.87% under AM 1.5 and 1 sun condition. It could be utilized for a low-cost and high-throughput process for DSSCs.